Surface waves in hexagonal micropolar dielectrics. (1st June 2016) - Romeo, Maurizio
Abstract: The propagation of surface waves on a dielectric half-space with hexagonal symmetry is studied on the basis of a recent modification of the micropolar theory of electroelastic continua. The model connects electric polarization to macro and micro-displacements via dipole and quadrupole densities due to the charge distribution in the continuum particle. The differential system derived in the linear wave problem accounts for coupling of acoustic modes with micro-rotational modes referred to polaritons. Bleustein–Gulyaev (BG) and Rayleigh waves are allowed in the half space and are shown to satisfy dispersion laws very similar to those obtained in the past from a phenomenological continuum theory of ferroelectrics. All the surface modes are dispersive and involve polarization via the microrotation gradient. The results prove the effectiveness of the present approach in order to represent electro-elastic coupling in dielectrics. The classical BG wave problem is recovered if microrotation gradient is neglected in the constitutive assumptions but the resulting mode is again dispersive. A similar reduction to the classical Rayleigh wave of linear elasticity allows for a flexoelectric contribution to polarization.